Does The Military Expenditure Hurt The Economic Growth? Evidence Derive From South Asian Countries - Budhathoki, Prem Bahadur; Dahal, Arjun Kumar; Bhattarai, Ganesh (Journal of Business and Management Review, 2024)
Research Aims: This study examines the impact of military spending onthe economic growth in South Asian countries.Design/methodology/approach: It uses the 134 unbalanced data points ofsix South Asian countries collected from the various reports of the WorldBank. Descriptive and exploratory research designs are used. It is basedon the positivist research philosophy. Some statistical and econometrictools like descriptive statistics, panel unit root test, Johnsen and Kaoresidual cointegration test, and panel ARDL model are used to explorethe impact of military expenditure, inflation rate, unemployment rate,and gross capital formation on the economic growth of South Asiancountries.Research Findings: Inflation has a positive effect on economic growth inthe long run but a negative impact in the short run. Military expenditurehas a positive effect in the long run but a negative impact on economicgrowth; the unemployment rate is negative, and gross capital formationpositively impacts economic growth in the long and short run in SouthAsian Countries. Military spending does not significantly affect economicprogress in the long run, but military expenditure hurts economic growthin the short run. One unit increase in military spending results from a0.633 percent decrease in the GDP growth of South Asian countries. Theyouth unemployment rate negatively impacts economic growth in theshort and long run. One unit increase in the unemployment rate resultsfrom 0.093 and 0.319 unit decrease in economic growth in the long andshort run, respectively. Likewise, one unit increase in capital formationand inflation rate results from 0.203 and 0.116 unit increase in GDPgrowth in the long run, respectively. The inflation rate negatively impactseconomic growth in the short run. One unit increase in inflation rateresults from 0.191 unit decrease in GDP growth in short-run. Prioritizestrategies that mitigate short-term negative impacts of inflation andmilitary expenditure while fostering long-term economic growth throughinvestment in capital formation and addressing youth unemployment inSouth Asian countries.Keywords: Inflation, unemployment, panel data, Keynesian stimulushypothesis, stagnation